2019
DOI: 10.1038/s41598-019-55382-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic deregulation of GATA3 in neuroblastoma is associated with increased GATA3 protein expression and with poor outcomes

Abstract: To discover epigenetic changes that may underly neuroblastoma pathogenesis, we identified differentially methylated genes in neuroblastoma cells compared to neural crest cells, the presumptive precursors cells for neuroblastoma, by using genome-wide DNA methylation analysis. We previously described genes that were hypermethylated in neuroblastoma; in this paper we report on 67 hypomethylated genes, which were filtered to select genes that showed transcriptional over-expression and an association with poor prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 59 publications
(72 reference statements)
1
18
0
Order By: Relevance
“…The largest such coefficient in the gene-wide GATA3 task trained on METABRIC-(LumA) belonged to MEGF10 (Additional file 3 : Figure S2), which has been previously implicated in cancer processes downstream of GATA3 [ 45 ]. MEGF10 was also weighted heavily in the best found subgrouping task, having the 37th largest absolute magnitude out of 13018 genes considered by the model.…”
Section: Resultsmentioning
confidence: 99%
“…The largest such coefficient in the gene-wide GATA3 task trained on METABRIC-(LumA) belonged to MEGF10 (Additional file 3 : Figure S2), which has been previously implicated in cancer processes downstream of GATA3 [ 45 ]. MEGF10 was also weighted heavily in the best found subgrouping task, having the 37th largest absolute magnitude out of 13018 genes considered by the model.…”
Section: Resultsmentioning
confidence: 99%
“…In these neuroblastoma cell lines, the DNA methylation level of the GATA3 gene locus was lower than that in normal human neural crest cells [32]. Subsequent analysis of clinical relevance revealed that high GATA3 expression tended to be associated with poor prognosis, indicating a close correlation between GATA3 expression levels and the clinical properties of neuroblastomas [32]. As an-ticipated, GATA3 siRNA (small interfering RNA) knockdown in neuroblastoma cell lines inhibited proliferation and increased apoptosis [31].…”
Section: Gata3 and Dna Methylation In Neuroblastomamentioning
confidence: 96%
“…Recent genome-wide studies have characterized broad alterations in DNA methylation status in a series of neuroblastoma cell lines [31]. In these neuroblastoma cell lines, the DNA methylation level of the GATA3 gene locus was lower than that in normal human neural crest cells [32]. Subsequent analysis of clinical relevance revealed that high GATA3 expression tended to be associated with poor prognosis, indicating a close correlation between GATA3 expression levels and the clinical properties of neuroblastomas [32].…”
Section: Gata3 and Dna Methylation In Neuroblastomamentioning
confidence: 99%
“…Analysis of the action of neuroblastoma PHOX2b variants in developing sympathetic neurons demonstrated their stimulatory effect on neuroblast proliferation combined with dedifferentiation indicating routes to malignancy modulated by PHOX2b in combination with HAND2 (Reiff et al 2010 ). Studies for other transcription factors of the network directing sympathetic neuron differentiation and their role in neuroblastoma exist for GATA3 (Almutairi 2019 ; Moriguchi 2021 ) and ASCL1 (Wang et al 2019 ; Ali et al 2020 ).…”
Section: Domains Of Progress In Understanding the Generation Specification And Connectivity Of Sympathetic Neuron Classesmentioning
confidence: 99%